Optimalisasi Peran Humas Pemerintah Dalam Meningkatkan Branding Pariwisata Bandung - Tsaqif, Gattan Qilabi; Hidayah, Hanifah Ulfa Tri; Al Firza, Chalifa Al Firza; Putri Ananda; Zebua, Winda Dwi Astuti (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
Tourism is a vital sector in the economic development of Bandung City. With its status as a member of the UNESCO Creative Cities Network (UCCN) in the design category, Bandung has great potential to become a leading tourist destination. This study aims to analyze the role of Government Public Relations in optimizing tourism branding through the “Stunning Bandung” program. This program is designed to increase the attractiveness of the city by utilizing creative campaigns, digital innovation, and cross-sector collaboration. Government Public Relations plays a role as a driving force in tourism promotion, building two-way communication with the public, and creating a positive narrative to improve the city’s image. The research method uses a literature review from various relevant sources, including scientific journals and government reports. The results of the analysis show that optimizing the role of Government Public Relations through the “Stunning Bandung” program is able to increase public awareness of local tourism potential and strengthen Bandung’s image as a creative destination. However, there are still several challenges, such as budget constraints and less than optimal cross-sector coordination. Therefore, a more integrated and collaborative communication strategy is needed to support the success of Bandung City’s tourism branding in a sustainable manner. Keywords: Bandung City, Government Public Relations, Tourism Branding, Stunning Bandung.